MAGNETIC RESONANCE IMAGING DIAGNOSIS OF INFLAMMATORY CHANGES OF THE AXIAL SKELETON IN ANKYLOSING SPONDYLITIS - A. V. Smirnov; Sh. F. Erdes (Научно-практическая ревматология, 2016)
As of now, magnetic resonance imaging (MRI) ranks high in the early diagnosis of inflammatory changes in the musculoskeletal system. The uniqueness of MRI is that this diagnostic technique can detect the signs of active and inactive inflammation at the pre-radiological stage of the disease, i.e. before the onset of radiological symptoms of sacroiliitis and the formation of spinal syndesmophytes. At the same time there is evidence that there is a temporary association between active inflammation and the development of radiological changes in the joints.The detection of bone marrow edema in the subchondral portions of bone tissue is of great importance not only for diagnosing the disease and verifying inflammatory activity, but also for predicting the development of chronic arthritis, choosing a treatment option, and evaluating the efficiency of performed therapy.Based on their long-term experience, the authors provided explanations of the MRI pattern of active and inactive chronic sacroiliitis and spondylitis, which can considerably facilitate the early diagnosis of injury to the sacroiliac joints and vertebral column in patients with ankylosing spondylitis.